ORGANIZATIONAL CULTURE AND WORK INNOVATION IN IMPROVING NURSING SERVICE QUALITY IN THE MAKKAH HEALTH CLUSTER, SAUDI ARABIA, 2026 - Khadija Lafi Aljarary; Hafizah Che Hasan (PT. Jurnal Center Indonesia Publisher, 2026)
Nursing service quality is a critical determinant of healthcare performance. Organizational culture and work innovation are recognized as key organizational factors influencing service quality, yet empirical evidence in cluster-based healthcare systems remains limited. This study examines the relationship between organizational culture and work innovation in improving nursing service quality in the Makkah Health Cluster, Saudi Arabia 2026. A quantitative cross-sectional design was employed involving 312 registered nurses selected through stratified random sampling. Data were collected using validated questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 4). Organizational culture significantly influences work innovation (β = 0.52, p < 0.001) and nursing service quality (β = 0.41, p < 0.001). Work innovation also significantly affects nursing service quality (β = 0.46, p < 0.001). Work innovation partially mediates the relationship between organizational culture and nursing service quality. The model explains 67% of variance in nursing service quality (R² = 0.67). Organizational culture improves nursing service quality directly and indirectly through work innovation. Strengthening organizational culture and fostering innovation are essential strategies for healthcare service improvement